Penguatan Peran Dewan Keamanan PBB dan Efektivitas Intervensi Dalam Penegakan Hukum Humaniter - Mustamin, Mustamin; Susilo, Tarsisius; Setiawan, Iwan; Erlangga , Aqsa (Jurnal sosial dan sains, 2025)
The United Nations Security Council (UNSC) holds the primary mandate to maintain international peace and security; however, the effectiveness of its interventions in responding to serious violations of international humanitarian law (IHL)—including genocide, war crimes, and crimes against humanity continues to exhibit significant shortcomings. This study aims to evaluate the politico-legal determinants that affect the effectiveness of the UNSC and to formulate a transformative and adaptive institutional policy approach in response to the dynamics of contemporary conflicts. Employing a qualitative methodology, the research utilizes document analysis, normative review, and institutional evaluation based on case studies such as Syria, Libya, and Darfur. The findings reveal that the dominance of the veto power, weak institutional interoperability, and the absence of evidence-based compliance mechanisms are among the main factors contributing to the Council’s ineffectiveness in enforcing IHL. A normative-operational interoperability model is proposed as a new conceptual approach to integrate legal, technical, and responsive aspects within intervention mandates. It is recommended that institutional reform of the UNSC include limiting veto use in cases of mass atrocities, establishing a humanitarian law verification unit, and integrating predictive digital systems as part of mandate strengthening. Such reforms are essential to ensure the continued relevance and credibility of the UNSC within the future architecture of global security governance.